PENYUSUNAN MARKETING PLAN BAGI USAHA KERAJINAN TANGAN IBU-IBU DI DESA TATAH PAMANGKIH KABUPATEN BANJAR - Rahmi Widyanti; Aida Vitria; Susiladewi Susiladewi (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2019)
The level development of entrepreneurs in Indonesia is very slow. This is influenced by attention the government to its citizens still lacking. We can take the example of one of the government's policies, import salt, chili, rice etc. Is it appropriate for the State of Indonesia as an agricultural country with the dawn of rice cultivation such imports. This situation to make farmer family felling down. Government attention is needed to empower people to improve the entrepreneurial spirit. Especially in developing informal business communities of the handmade product. However, it is also the role of public institutions and universities by providing socialization and counseling, in order to accelerate the empowerment felt by the public and obtain maximum benefit in managing the business. This is effort to increase handmade production by moms community, the soul of entrepreneurs need to be given knowledge about the preparation of the marketing plan format.